Acupuncture at GV20 and ST36 Improves the Recovery of Behavioral Activity in Rats Subjected to Cerebral Ischemia/Reperfusion Injury - Yang, Yang; Deng, Peiying; Si, Yingkui; Xu, Hong; Zhang, Jianmin; Sun, Hua (Frontiers in Behavioral Neuroscience, 2022)
Traditional acupuncture and electroacupuncture (EA) have been widely performed to treat ischemic stroke. To provide experimental support for the clinical application of acupuncture to ameliorate post-stroke sequelae, in this study, we investigated the therapeutic effect of acupuncture and EA on CIRI following middle cerebral artery occlusion (MCAO) in rats. The animals were randomly divided into five groups: sham-operated (S), model (M), traditional acupuncture (A) treatment, electroacupuncture (EA) treatment, and drug (D; edaravone) therapies. Neurological behavioral characteristics (neurological deficit score, forelimb muscle strength, sensorimotor function, body symmetry, sucrose consumption, and mood) were examined in all the groups on days 1, 3, 5, and 7 after reperfusion. Expressions of vascular endothelial growth factor (VEGF) and hypoxia-inducible factor-1α (HIF-1α) were detected by immunohistochemistry. Both acupuncture and EA significantly reduced neurological deficits and improved forelimb muscle strength, sensorimotor function, body symmetry recovery, and neurovascular regeneration in the rats after ischemia/reperfusion injury. The efficacies of both acupuncture and EA were comparable to that of edaravone, a commonly used medicine for stroke in the clinic. Thus, our data suggest that acupuncture and EA therapy at acupoints GV20 and ST36 might represent alternative or complementary treatments to the conventional management of ischemic stroke, providing additional support for the experimental evidence for acupuncture therapy in clinical settings. In summary, EA might provide alternative or complementary treatment strategies for treating patients with apoplexy in the clinic. However, potential mechanisms underlying the role of acupuncture require further investigation.